Seasonal changes of physical (motor) activities in professional Greek football players - Smpokos, Emmanouil; Mourikis, Christos; Linardakis, Manolis (Akademia Wychowania Fizycznego w Poznaniu)
Introduction. Football is an activity demanding of each of the energy systems. There have been many studies that have described the match activity profiles of top-level soccer players during an annual season, but few have try to evaluate seasonal-variations month-by-month. Aim of Study. Τhis study aimed to investigate the seasonal variations in physical (motor) activities of elite professional Greek football players in official-matches of national League and in European matches by separated a season (2016-2017) in eight-month-period. Material and Methods. Twenty-seven players were recruited using Global-Positioning-System Technology (GPS). Total-distance (TD; km), high-speed-running (HSR; >19.8 km/h), very-high-intensity-speed-running (VHS;19.8-25.2 km/h), maximal-sprinting (MS; >25.2 km/h), relative-distance/time (D/T), high-metabolic-load-distance (HMLD; meters),dynamic-stress-load (DSL), and number of accelerations-decelerations were measured. Multivariate analysis was performed. Results. Performance variations showed significant changes in all measurements (p < 0.05) noted from preparation phase (June--August) to end-season with the exception of DSL and HMLD. The greater TD was recorded in January and the lowest during preparation phase (10.4 vs. 9.0 km, p < 0.001) while higher average levels in HSR were found in February’s matches in relation to November’s (654.6 vs. 389.9 meters, p < 0.001) or in MS (147.4vs. 68.9 meters, p = 0.004). Increase from the preparation phase over the seven-time-periods was found in VHS (+15.6%; p-trend< 0.001) or in TD (+11.8%; p-trend = 0.012). However decreases were observed in D/T (–8.8%; p-trend < 0.001) or in number of sprint-runs (–3.4%; p-trend = 0.028). Significant interactions (p < 0.001) were also revealed between playing position and the time periods, in accelerations and decelerations measurements (η2 ≥ 0.20). Conclusions. Significant changes to most of the motor activities variations were observed between the preparation-phase and mid-season (February-March). The analyses of physical loads on soccer players during official matches are highly useful for training individualization, as providing a tool for effective planning in matches’ management, recording the loads on players and can therefore aid to avoid the risk for severe injuries.
Keywords: football; GPS; match analysis; motor activities